PERAN DANA GAMPONG DALAM PEMBANGUNAN PERTANIAN DI KABUPATEN ACEH UTARA - Budi, Setia Budi (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2023)
Village funds are funds sourced from the state budget (APBN) which are prioritized for the implementation of development and community development based on the potential in the village. prioritized for the implementation of development and community development based on the potential that exists in the village. Muara Batu Sub-district is one of the recipients of the village fund or the largest ceiling, has a large agricultural area, the majority of the farming community work as farmers but the initial survey of village funds for agriculture was only a small part realized in North Aceh District. Gampong Cot Trueng, Meunasah Baro, Teupin Banja are the highest, medium and lowest ceiling recipients selected as research areas. This study aims to determine the contribution of gampong funds in agricultural development in Muara Batu sub-district and to identify the role of gampong funds in agricultural development in Muara Batu sub-district. The analysis method used is descriptive qualitative. The results showed that the role of gampong funds in agricultural development in 2018 contributed 42%, in 2019 contributed 11%, in 2020 contributed 44%, and the identification of the role of gampong funds in agricultural development in 2020 contributed 44%. 2020 contributed 44%. and identification of the role of village funds in agricultural development, namely procurement of seeds, procurement of fertilizers, procurement of agricultural capital, training of horticultural crops, construction of irrigation channels, construction of tertiary channels, construction of farm roads, construction of agricultural centers. The contribution and identification of the role of village funds in agricultural development was able to increase rice production from 7.2 tons/ha to 8.5 tons/ha.